Comparison studies among the methods used in isolating the GSH from baker yeast - Mohamed Salleh, Mohamad Ramlan; Farouk, Abd. Elaziem; Jamal, Parveen; Hashim, Yumi Zuhanis Has-Yun; Salleh, Rohani; Hasim, Haslinda (Asian Network for Scientific Information, 2005)
The purpose of this study was to make a comparison among the methods used in isolating the GSH from baker yeast. This was done by comparing the optimum values of operating parameters such as the yeast concentration, processing temperature and the isolation time of each of the isolation methods used (Autolysis, Ultrasonic and Homogenizer). Among the three methods, Autolysis method produced the highest GSH concentration of 49.263 μmol mLG1 (15.14 g LG1) followed by Homogenizer method (18.33 μmol mLG1 or 5.63 g LG1) which is slightly higher than that of the Ultrasonic method (18.13 μmol m L G 1 or 5.57 g L G 1). The different occurred probably due to the different of the isolation time applied to the three methods. The same duration time couldn’t be used because it will increase the temperature of the sample higher that the optimum temperature of some of the methods. Unlike Ultrasonic and Homogenizer methods, the temperature for Autolysis method could be maintained within 1 h while for Homogenizer and Ultrasonic methods the temperature could only be maintained within 30 and 15 sec, respectively. The step down arrangement from best to worst for lab scale production was Autolysis>Homogenizer>Ultrasonic method. Autolysis was the best but the isolation time is longer compared to the other so that in large scale production, Homogenizer seems to be the best method due to the economical perspective. Ultrasonic is also can be considered as an excellent method but expensive compared to others.